Long-term Outcome of Endovascular Treatment for Mycotic Aortic Aneurysm. (October 2017) - Luo, C.-M.; Chan, C.-Y.; Chen, Y.-S.; Wang, S.-S.; Chi, N.-H.; Wu, I.-H.
Abstract : Objective/Background: Endovascular repair (EVAR) of mycotic aortic aneurysm (MAA) has become an alternative treatment for high risk patients. The aim of this study was to evaluate long-term survival and outcomes. Methods: Retrospective analysis of 40 consecutive patients with MAAs undergoing EVAR and subsequent intravenous antibiotic treatment between September 2009 and April 2015. Follow-up was truncated on 30 April 2015. Uni- and multivariate logistic regression were used to assess risk factors of adverse outcomes. Cumulative survival was calculated using the Kaplan–Meier method. Results: Median age at repair was 73 years (range 48–88 years) and 31 (77%) were men. Eleven (27%) patients were infected with Salmonella, 12 (30%) with non- Salmonella species, and 17 (42%) had negative cultures. Anatomical locations included the aortic arch/thoracic area in 10 (25%), the paravisceral area in seven (17%), and the infrarenal area in 23 (57%). Ten (25%) patients presented with aneurysm rupture and underwent emergency repair. Median follow-up was 25 months (range 1–69 months). Cumulative 1 and 5 year survival rates were 71% and 53%, respectively. Persistent or recurrent infection occurred in 20% ( n  = 8). Patients with persistent infection were treated with long-term medical therapy, but all died (75%; n  = 6) within 6 months of repair. No survival difference was found between patients with or without Salmonella infections. However, there was a trend toward better survival in culture negative patients. Conclusion: EVAR of MAA is an acceptable alternative treatment of MAA. However, persistent infection after endovascular treatment does occur and is often fatal without surgical treatment.